Analysis of the predictive variables of socially responsible consumption. Issue 3 (21st October 2021) - Palacios‐González, María Manuela; Chamorro‐Mera, Antonio
Abstract: Achieving the Sustainable Development Goals proposed by the UN for 2030 implies designing strategies that promote socially responsible consumption. The effectiveness of these strategies will depend on understanding the variables that influence socially responsible behaviour. We must also bear in mind that these variables and this behaviour are of a dynamic, multidimensional and non‐universal nature. The objective of this work is to identify how three attitudinal variables (emotional engagement, perceived consumer effectiveness and perception of personal gain) influence socially responsible consumption, through a model of structural equations. To do this, a survey was conducted of 415 Spanish consumers. The results reflect that socially responsible consumption is mainly explained by emotional engagement and to a lesser extent by perceived consumer effectiveness. In contrast, it is not influenced by perception of personal gain.